Application of BMSCs-coated PLGA/type I collagen composite mesh in intraperitoneal onlay mesh repair using a rat ventral incisional hernia model - He, Mingliang; Pan, Yi; Li, Jiayi; Qi, Yaqin; Zhu, Kangbei; Zhang, Fangjie (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeThis study aimed to address the limitations of synthetic meshes in incisional hernia repair by developing a bioactive composite mesh combining poly(lactic-co-glycolic acid) (PLGA), type I collagen, and bone marrow mesenchymal stem cells (BMSCs).MethodsThe PLGA scaffolds, fabricated via freeze-drying, were modified with collagen to enhance biocompatibility and loaded with BMSCs to promote tissue regeneration. In vitro and in vivo evaluations in a rat ventral hernia model assessed biomechanical properties, anti-adhesion efficacy, and tissue integration.ResultsThe PLGA-Collagen I-BMSCs mesh exhibited superior anti-adhesion performance, reduced inflammatory cell infiltration by 73.3%, and enhanced neovascularization compared to commercial meshes (Sepramesh™ and Parietex™). BMSCs modulated TGF-β1/Smad3 signaling to mitigate fibrosis, while collagen alignment improved mechanical recovery. The composite mesh degraded at a rate matching tissue regeneration, with 10% PLGA maintaining structural integrity for 20 weeks. Histological analysis revealed organized collagen deposition and minimal adhesions (Nair grade 0–1 in 100% of cases).ConclusionThese findings highlight the potential of the PLGA-Collagen I-BMSCs composite as an innovative intraperitoneal onlay mesh (IPOM) solution, offering mechanical stability, anti-adhesive properties, and regenerative bioactivity. This strategy shifts hernia repair from passive support to active tissue regeneration, providing a foundation for next-generation hernia repair materials.